Faktor Merokok dengan Kejadian Stroke di Rumah Sakit Santa Elisabeth Medan - Pomarida Simbolon; Nagoklan Simbolon; Magda Siringo-ringo (Jurnal Kesehatan Manarang, 2018)
Background: Stroke is a serious disease problem and can lead to obedience and death. The high prevalence of stroke at Santa Elisabeth Hospital Medan can be seen from the number of outpatients and inpatients increased. Stroke that occurs caused by lifestyle is not good and one of them is the factor of smoking. Objective: to know the relationship of the smoking factor with the incidence of stroke at Santa Elisabeth Hospital Medan. Method: The type of research used is cross-sectional to study the relationship of the smoking factor with the incidence of stroke at Santa Elisabeth Hospital Medan Year 2016. The sample in the study amounted to 34 people with purposive sampling technique. The data were collected by using questionnaires. Data analysis was done by chi-square test. Result: = the results obtained 70.6% of patients with stroke occurs caused by smoking and stroke occurs in the first attack 52.9%. The result of chi-square statistic test obtained p-value = 0.008 (p <0.05). There is a relationship of the smoking factor with the incidence of stroke in Hospital Santa Elisabeth Medan. Conclusion: it is advisable for the nurse to provide health education on smoking causes of stroke and advise the patient to maintain a healthy lifestyle and collaborate with the doctor, physiotherapy in order to prevent the occurrence of recurrent stroke.